2022
DOI: 10.1021/acsenergylett.2c01766
|View full text |Cite
|
Sign up to set email alerts
|

(3-Aminopropyl)trimethoxysilane Surface Passivation Improves Perovskite Solar Cell Performance by Reducing Surface Recombination Velocity

Abstract: We demonstrate reduced surface recombination velocity (SRV) and enhanced power-conversion efficiency (PCE) in mixed-cation mixed-halide perovskite solar cells by using (3-aminopropyl)­trimethoxysilane (APTMS) as a surface passivator. We show the APTMS serves to passivate defects at the perovskite surface, while also decoupling the perovskite from detrimental interactions at the C60 interface. We measure a SRV of ∼125 ± 14 cm/s, and a concomitant increase of ∼100 meV in quasi-Fermi level splitting in passivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…The pc-AFM measurements show that despite the passivated layer, the films do exhibit photocurrent through a subset of pixels, indicating that devices can transport charge in a solar cell despite having an insulating top layer. These results are consistent with other recent work showing that perovskite films and their charge extraction layers are generally conductive enough that only a subset of the perovskite film area needs to be in electronic contact with the extraction layers. , However, as presented in the plot in Figure S9, all passivated samples exhibit currents significantly lower than those in the unpassivated (3D) film, which is an observation that is expected if there is full coverage of the underlying layer both via vapor and via solution. Heterogeneity is observed in all treated films even at higher magnifications, as shown by the 3 μm × 3 μm pc-AFM images (Figure S10).…”
supporting
confidence: 91%
“…The pc-AFM measurements show that despite the passivated layer, the films do exhibit photocurrent through a subset of pixels, indicating that devices can transport charge in a solar cell despite having an insulating top layer. These results are consistent with other recent work showing that perovskite films and their charge extraction layers are generally conductive enough that only a subset of the perovskite film area needs to be in electronic contact with the extraction layers. , However, as presented in the plot in Figure S9, all passivated samples exhibit currents significantly lower than those in the unpassivated (3D) film, which is an observation that is expected if there is full coverage of the underlying layer both via vapor and via solution. Heterogeneity is observed in all treated films even at higher magnifications, as shown by the 3 μm × 3 μm pc-AFM images (Figure S10).…”
supporting
confidence: 91%
“…Previous work from our group has shown that (3-aminopropyl)­trimethoxysilane (APTMS) significantly reduces non-radiative recombination in halide perovskite semiconductors. , Because halide migration often involves halide vacancies, , the same sites that are often targeted by chemical surface passivation, , ,, we hypothesize that surface passivation using the specific chemistry offered by molecules, such as APTMS, should also suppress halide migration.…”
mentioning
confidence: 98%
“…We refer to these as-grown films as “control” or “unpassivated” perovskites. To prepare passivated perovskite films, we exposed the films to APTMS for 5 min at room temperature in a low-vacuum chamber as previously described. , We verified that the films had a perovskite structure using X-ray diffraction (XRD) (panels a and b of Figure S1 of the Supporting Information). Ultraviolet–visible (UV–vis) absorption data are consistent with a bandgap of ∼1.7 eV, confirming the target compositions of Cs 0.22 FA 0.78 Pb­(I 0.85 Br 0.15 ) 3 and Cs 0.17 FA 0.83 Pb­(I 0.75 Br 0.25 ) 3 (panels c and d of Figure S1 of the Supporting Information).…”
mentioning
confidence: 99%
“…To date, many strategies for improving the photovoltaic performance and stability of PSCs have been reported, including mixed-halide engineering, , surface and interface passivation, additive engineering, selection of the charge-transport material, , and encapsulation . Among the aforementioned methodologies, additive engineering is considered the most effective and promising option because of the well-established intrinsic coordination ability of lead cations in the [PbI 6 ] 4– octahedral matrix of perovskites.…”
mentioning
confidence: 99%